Two Ḥadīth Scholars from Java: Study of Shaykh Mahfudz at-Tarmasi and Shaykh Hasyim Asy'ari - Muhammad Abdul Kharis (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
A study of ḥādīth is the one not as well-known and rich as the study of other Islamic sciences such as tafsīr and fiqh. In fact, the study of ḥādīth is very necessary to do and to develop continously, including the study of its scholars. In this study, the writer focuses on studying two figures in the field of ḥādīth coming from Java: Sheikh Mahfudz at-Tarmasi and Sheikh Hashim Asy'ari. This study uses a qualitative descriptive research method with data sourced from literature. The conclusion highlights that both Sheikh Mahfudz at-Tarmasi and Sheikh Hasyim Asy’ari are important figures in the study of ḥādīth in the Nusantara region. Sheikh Mahfudz, with his books entitled Manhaj Dzawi an-Nadhar, Kifayah al-Mustafid, al-Minhah al-Khairiyyah, and al-Khil’ah al-Fikriyyah, clearly and specifically presents studies on ḥādīth sciences, both in terms of riwayah (narration) and dirayah (understanding), as a theoretical study. Meanwhile, Sheikh Hashim in his book entitled Risalah ahl as-Sunnah wa al-Jama’ah presents the narrations of ḥādīth as a way to unite the Muslim community in the circle of ahlussunnah wal jama'ah. Both of them are Islamic figures of the archipelago having contributed to the regeneration of scholars, especially ḥādīth scholars. As conveyed by classical scholars, sanad is one of the important aspects in the transmission of knowledge (ḥādīth). So this tradition must be preserved, especially in the world of Islamic boarding schools. However, it should be underlined that ḥādīth is not merely a literal text but it, with the values ​​contained in it, also must always be brought to life in everyday life according to the socio-cultural context.